Upaya Meningkatkan Kemampuan Teknik Dasar Atletik Nomor Lari Sprint Siswa SMP melalui Penggunaan Media Audiovisual - Fikri Lutfhi; Ega Trisna Rahayu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
ABSTRACT This study aims to determine the extent to which efforts to improve basic athletic technical skills in the sprint number of junior high school (SMP) students through audiovisual media. This research method used experiments. The population used in this study were students of Islamic Junior High School Sahabat Ilmu Karawang. Likewise, the samples used were all students of class VII SMP Islam Sahabat Ilmu Karawang. With a total sample of 6 students. Data collection techniques using pre-test and post-test. The results of this study indicate that there is an increase in using audiovisual media. Namely, the Kolmogorov-Smirnov normality test results with the Shapiro-Wilk test > 0.05. It can be interpreted that the data is usually distributed, and the results of the calculation of the paired sample test obtained sig. (2-tailed) of 0.00 where if sig. (2-tailed) < 0.05 The conclusion is that audiovisual media affects efforts to improve basic athletic techniques in sprint running numbers. Keywords: Athletics, audio visual, sprints